Bankruptcy, Investment, and Financial Constraints: Evidence from a Post-Transition Economy - Martin Pospíšil; Jiří Schwarz (Charles University in Prague, Institute of Economic Studies (IES), 2014)
In this paper we use balance-sheet data and information on bankruptcy to study the relationship between investment, financial constraints, and bankruptcy in a posttransition country. Our data constitute a dynamic panel and cover the period 2006-2011, which also allows us to study the impact of the 2008 crisis on Czech companies. Using investment-cash flow sensitivity to analyze financial constraints we find there is robust evidence that cash flow and the level of debt have a positive and significant impact on the investment rate. By taking a closer look at individual subsamples we reveal that the existence of financial constraints, proxied by investment-cash flow sensitivity, is evident mainly after 2008 and in small and medium-sized enterprises. At the same time, we do not uncover any evidence that firms going bankrupt during our observed period faced more severe financial constraints. Moreover, companies going bankrupt had significantly higher levels of external debt and bank loans, which indicates that they may have been, in fact, less constrained than others.
Keywords: D22; D92; E22; G32; 330; bankruptcy; cash flow; credit rationing; financial constraints; investment; post-transition economy